ChemInform Abstract: Rare Earth—Transition Metal—Cadmium Intermetallics ‐ Crystal Chemistry and Physical Properties. Issue 2 (14th January 2014) - Tappe, Frank; Poettgen, Rainer
Abstract Review: 90 refs.